National Athletic Trainers' Association position statement: Facilitating work-life balance in athletic training practice settings - Mazerolle, S. M.; Pitney, W. A.; Goodman, A.; Eason, C. M.; Spak, S.; Scriber, K. C.; Voll, C. A.; Detwiler, K.; Rock, J.; Cooper, L.; Simone, E. (Journal of Athletic Training, 2018)
Objective: To illustrate the concept of work-life balance and those factors that influence it and to provide recommendations to facilitate work-life balance in athletic training practice settings. To present the athletic trainer with information regarding work-life balance, including those factors that negatively and positively affect it within the profession.